Involvement of the TRPV1 receptor in plasma extravasation in airways of rats treated with an angiotensin-converting enzyme inhibitor. (December 2016) - de Oliveira, Janiana Raíza Jentsch Matias; Otuki, Michel Fleith; Cabrini, Daniela Almeida; Brusco, Indiara; Oliveira, Sara Marchesan; Ferreira, Juliano; André, Eunice
Abstract: Angiotensin-converting enzyme inhibitors (ACEIs) are widely used in the treatment of hypertension, congestive heart failure and renal disease, and are considered relatively safe and generally well-tolerated drugs. However, adverse effects of ACEIs have been reported, including non-productive cough and angioedema, which can lead to poor adherence to therapy. The mechanisms by which ACEIs promote adverse effects are not fully elucidated, although increased bradykinin plasma levels following ACEI therapy seem to play an important role. Since bradykinin can sensitise the transient potential vanilloid receptor 1 (TRPV1), we investigated the role of TRPV1 in plasma extravasation in the trachea and bronchi of rats treated with the ACEI captopril. We observed that intravenous (i.v.) administration of captopril did not cause plasma extravasation in the trachea or bronchi of spontaneously breathing rats, but induced plasma extravasation in the trachea and bronchi of artificially ventilated rats. The intratracheal (i.t.) instillation of capsaicin or bradykinin also induced an increase in plasma extravasation in the trachea and bronchi of artificially ventilated rats. As expected, capsaicin-induced plasma extravasation was inhibited by i.t. pretreatment with the TRPV1 selective antagonist capsazepine (CPZ) while bradykinin-induced plasma extravasation was reduced by i.t. pretreatment with the selective B2 receptor antagonist Icatibant, originally known as HOE 140 (HOE). Interestingly, bradykinin-induced plasma extravasation was also inhibited by CPZ. The pretreatment with HOE and CPZ, singly or in combination and at doses which do not cause inhibitory effects per se, significantly inhibited the plasma extravasation induced by captopril treatment in artificially ventilated rats. In addition, treatment with a high dose of capsaicin in newborn rats, which induces degeneration of TRPV1-expressing sensory neurons, abolished both capsaicin and captopril-induced plasma extravasation in artificially ventilated rats. In conclusion, our study identified that captopril treatment promoted sensitisation of TRPV1, via B2 receptor activation, inducing plasma extravasation in the airways of mechanically ventilated rats. The present findings add a new view about the role of TRPV1 in the plasma extravasation induced by captopril and could to contribute to the elucidation of mechanisms by which ACEI induces adverse effects on airways.